A retrospective study of the efficacy and safety of levofloxacin in children with severe infection - Junqi, Zhang; Jie, Cai; Jinglin, Wang; Jinmiao, Lu; Guoping, Lu; Yi, Wang; Zhiping, Li (Frontiers in Pediatrics, 2024)
Objectives Levofloxacin is widely used because of its broad spectrum antimicrobial activity and convenient dosing schedule. However, the relevance of its use in children remains to be investigated. The purposes of this study were to investigate the efficacy and safety of levofloxacin use in children with severe infections. Methods We conducted a retrospective observational study of patients <18 years of age who received levofloxacin intravenously in the PICU of our hospital from 2021 to 2022. Patient demographics, courses characteristics, clinical effectiveness, and adverse event correlations were extracted through retrospective tabular review. Results We included 25 patients treated with 28 coursess of levofloxacin. The mean age of these children treated with levofloxacin was 4.41 yr. Conversion of pathogenic microbiological tests to negative after levofloxacin treatment was detected in 11 coursess (39.29%). a decrease in inflammatory markers White blood cell or C-reactive protein counts was detected in 18 coursess (64.29%). A total of 57 adverse events occurred during the treatment period, of which 21 were possibly related to levofloxacin and no adverse events were probably related to levofloxacin. Conclusion The effectiveness of levofloxacin use in children with serious infections is promising, especially for the treatment of multidrug-resistant bacteria. Adverse events occurring during levofloxacin therapy in children are reported to be relatively common, but only a small percentage were possibly related to levofloxacin, and none were highly possibly related to levofloxacin.